THE SYMBOLIC MEANING OF KEMBANG URA DANCE IN THE SIDAKARYA MASK TRADITION: AN ETHNO-AESTHETIC STUDY - Dewa Ayu Galih Mas Narapadi; Ni Made Ruastiti; Kompiang Gede Widnyana (Institut Seni Indonesia Bali, 2026)
The Kembang Ura Dance is a contemporary work reinterpreting the flower-scattering ritual of the Sidakarya Mask, a vital component of Balinese Hindu ceremonies. This study examines how ritual actions are transformed into aesthetic choreography without losing spiritual depth or profaning sacred symbols. Employing a qualitative method with ethno-aesthetic and ethnochoreological approaches, the research analyzes the dance’s structure, creative process, and significance. The findings reveal that the dance transcends mere movement; it articulates symbols of purification, universal compassion, and ritual blessing. These meanings are embedded in its choreographic structure, vintage-inspired costumes, and its role as a ritual completer of Yadnya. The study concludes that Kembang Ura Dance serves as a model for ritual-based creative dance, successfully balancing modern aesthetics with the continuity of sacred values within the evolving landscape of contemporary Balinese culture.